Utilização de meios alternativos e diferentes tipos de recipientes no cultivo de Ankistrodesmus gracilis (Reinsch) Korshikov (Chlorophyceae) em laboratório - Sipauba-Tavares, Lucia Helena [UNESP]; Millan, Rodrigo Ney [UNESP]; Berchielli, Flávia de Almeida [UNESP]; de Souza Braga, Francisco Manoel [UNESP] (Universidade Estadual de Maringa, 2011)
A laboratory culture of Ankistrodesmus gracilis algae was evaluated by studying the biology of the species and its chemical composition in a traditional medium (CHU 12) and in two alternative culture media, NPK (20-5-20) and macrophyte (Eichhornia crassipes) + NPK, in three different types of recipients (fiberglass, carboy and plastic bag). First peak in the growth curve of Ankistrodesmus gracilis occurred on the ninth day in macrophyte + NPK medium (74.16 x 10 5 cells mL -1) in a fiberglass recipient. However, highest density (p < 0.01) was reported in medium CHU 12 (122.87 x 10 5 cells mL -1) in a plastic bag on the twelfth day. Cell density was over 70 x 10 5 cells mL -1 starting on the twelfth day. Growth rate of A. gracilis was similar (p > 0.05) in culture media in the three recipients. Protein and fiber were similar (p > 0.05) in the treatments, but lipids were higher (p < 0.05) in NPK. Nitrate, ammonia, total phosphorus and orthophosphate contents were over 1 mg L -1 in NPK (p < 0.01). Results show that alternative media, such as NPK and macrophyte + NPK, are possible for large-scale culture of A. gracilis cultured in three types of recipients. Costs are low, occupying less space when cultured in plastic bags and in the laboratory.
Use of alternative media and different types of recipients in a laboratory culture of Ankistrodesmus gracilis (Reinsch) Korshikov (Chlorophyceae)
Keywords: Algae; Biochemical composition; CHU 12; Growth; Macrophyte medium; NPK; ammonia; glass fiber; lipid; nitrate; phosphate; phosphorus; plastic; algal cell culture; algal growth; carboy; cell density; chemical composition; Chlorophyceae; CHU12; container; controlled study; culture medium; Eichhornia; growth curve; growth rate; laboratory; macrophyte; microbiology; nonhuman; protein content; algae; Ankistrodesmus gracilis; Eichhornia crassipes